Zaungäste : die Generation, die nach der Revolte kam - Mohr, Reinhard (S. Fischer, 1992)
Reinhard Mohr: "Zaungäste". Die Generation, die nach der Revolte kam. S. Fischer Verlag, Frankfurt am Main 1992. 222 S., br., 28,- DM